Pengaruh Kualitas Pelayanan dan Citra Merek Terhadap Kepuasan Pelanggan PT. Tri Karya Cemerlang (Study Kasus pada Karyawan PT. Nippon Indosari Corpindo) - Ana Karlina; Husni Mubarak (CIVITAS: Jurnal Studi Manajemen, 2022)
the purpose of this study was to determine whether there is an influence of service quality and brand image on customer satisfaction at PT. Tri Karya Cemerlang. The sample of this study was 52 people. Sampling using probability sampling with random sampling technique. The results showed that the coefficient of determination obtained by 0.882 or 88.2% showed that The Quality of Service and Brand Image was able to explain the variation in customer satisfaction in PT Tri Karya Cemerlang, while the remaining 11.8% was explained by other variables not studied in this study such as facilities, product quality, conformity between price and product, etc., The results showed that service quality partially had no effect on customer satisfaction, while brand image had a positive and significant effect on customer satisfaction, while simultaneously service quality and brand image had a positive and significant effect on customer satisfaction